A STUDY ON DIFFERENT PLANTS OF APOCYNACEAE FAMILY AND THEIR MEDICINAL USES - Islam, Md. Shahidul; Lucky, Rasheda Akter (Universal Journal of Pharmaceutical Research, 2019)
The apocynaceae family is one of the most medicinally diverse families in the plant kingdom and is a rich source for drugs that have found use both traditionally and in conventional medicine. The medicinal activity of these plants was due to the presence of alkaloids which were either indoline alkaloids or steroidal alkaloids. The family Apocynaceae consists of tropical trees, shrubs and vines. Characteristic features of the family are that almost all species produce milky sap. In traditional medicine, Apocynaceae species are used to treat gastrointestinal ailments, fever, malaria, pain and diabetes, including skin and ecto-parasitic diseases. Some are important timber species while many are planted as ornamentals. Non-medicinal uses include food, poisons, fodder, wood, ornamentals, dye and perfume. A total of 4600 species under 415 genera belonging to the family Apocynaceae were collected and identified. Species of Apocynaceae have been reported to possess anticancer and antimalarial properties. Species having cytotoxic activity include those of Catharanthus, Nerium, Plumeria, Tabernaemontana and Ichnocarpus. Catharanthusroseus is the most medicinally important plant in this family due to its use in the treatment of various types of cancers, other agents that have been derived from this family include the alkaloids reserpine and rescinamine which have been used against hypertension, others are the cardiac glycosides. Peer Review History: Received 7 December 2018; Revised 11 January 2019; Accepted 3 March 2019; Available online 15 March 2019 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewer(s) detail: Dr. Mohamed Said Fathy Al-Refaey , University of Sadat City, Menofia, Egypt, Mohamed.said@fop.usc.edu.eg Prof. Dr. Ali Gamal Ahmed Al-kaf , Sana'a university, Yemen, alialkaf21@gmail.com